(untitled) (Iraqi Journal of Civil Engineering, 2010)
This research investigates the efficiency of Ultrasonic Pulse Velocity (UPV) method in detecting voids and depth of cracks in concrete. Tests were performed to compare the accuracy between the direct and indirect method of Ultrasonic Pulse Velocity method (UPV) in detecting the location of defects. Three concrete prisms with fabricated void at a known location were used and tested at 28 day. Two other prisms were casted and tested to detect of crack depth in concrete, cracks at depth of 5 and 10 cm perpendicular to axis of beam were induced without actually breaking the beam. Test results indicate that direct and indirect methods can be used to assess the in-situ properties of concrete or for quality control on site, and the first and second method of determining the crack depth gave results with high accuracy while the results of third method were lower than the actual crack depth and for the forth method were higher than it. Therefor, we can use the average of the third and forth results to obtain the crack depth with good accuracy.